Formation of a hexagonal lattice structure by an R-form lipopolysaccharide of Klebsiella sp. - Kato, N (1985)
We extracted an R-form lipopolysaccharide (LPS) by the phenol-water method from Klebsiella sp. strain LEN-111 (O3-:KI-) and followed the changes in ultrastructure of the LPS during the extraction procedure. When the LPS was obtained from the water phase of an extract by addition of 2 volumes of 10 mM MgCI2-ethanol, it consisted of membrane pieces with a hexagonal lattice structure with a lattice constant of 14 to 15 nm. The lattice structure of the LPS was disrupted into short rods with sodium dodecyl sulfate, but the same hexagonal lattice structure was again formed by precipitation with 2 volumes of 10 mM MgCI2-ethanol. The LPS preparation after two cycles of treatment by the phenol-water method, which contained no detectable amounts of proteins, kept an unaltered ability to form the hexagonal lattice structure. Extensive treatment with pronase and extraction with chloroform did not impair the ability of the LPS preparation to form the lattice structure. When the other salts, NaCI, CaCI2 or Zn(CH3COO)2, were used for precipitation of the LPS with ethanol in place of MgCI2, the LPS did not form the hexagonal lattice structure. However, if the LPS precipitated with NaCI-ethanol was converted to the magnesium salt form after it was electrodialyzed, it formed the same hexagonal lattice structure as the LPS precipitated with MgCI2-ethanol. From these results, it was concluded that the R-form LPS has the ability of in vitro self-assembly into a hexagonal lattice structure in the presence of Mg2+ without the help of other components such as proteins and free lipids from outer membrane.